2014
DOI: 10.1007/s00429-013-0695-3
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of speech perception decline in aging

Abstract: Speech perception difficulties are common among elderlies; yet the underlying neural mechanisms are still poorly understood. New empirical evidence suggesting that brain senescence may be an important contributor to these difficulties has challenged the traditional view that peripheral hearing loss was the main factor in the etiology of these difficulties. Here, we investigated the relationship between structural and functional brain senescence and speech perception skills in aging. Following audiometric evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
45
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 110 publications
12
45
1
2
Order By: Relevance
“…Another, more likely possibility is that decline in speech accuracy is related to a decline in the neural planning and control of speech movements. Consistent with this hypothesis, recent studies from our group have shown important agerelated changes in the structure and function of brain areas involved in speech motor control, including the premotor cortex and the supplementary motor area (Bilodeau-Mercure et al 2014;Tremblay et al 2013). Given the importance of communication in aging, and the fact that speaking is intrinsically a sequential behavior, further research is needed to better understand the cause of these sequencing difficulties.…”
Section: Speech Productionsupporting
confidence: 59%
“…Another, more likely possibility is that decline in speech accuracy is related to a decline in the neural planning and control of speech movements. Consistent with this hypothesis, recent studies from our group have shown important agerelated changes in the structure and function of brain areas involved in speech motor control, including the premotor cortex and the supplementary motor area (Bilodeau-Mercure et al 2014;Tremblay et al 2013). Given the importance of communication in aging, and the fact that speaking is intrinsically a sequential behavior, further research is needed to better understand the cause of these sequencing difficulties.…”
Section: Speech Productionsupporting
confidence: 59%
“…This was done in order to avoid priming subvocal rehearsal during the speech perception task. The speech perception in noise task has been reported elsewhere (Bilodeau-Mercure et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Here we report the data from 15 young adults, whereas Bilodeau-Mercure et al (2014) reported the data for a subset (11) of these participants, who performed the speech perception in noise task.…”
mentioning
confidence: 99%
“…Moreover, Eickhoff, Heim, Zilles, and Amunts (2009) recently suggested that the left AI is part of a network with the cerebellum, basal ganglia and cortical motor system involved in speech preparation and execution. Aging studies have shown that decline in speech skills are accompanied by functional and anatomical changes in the AI (Bilodeau-Mercure et al, 2014; Tremblay et al, 2013). In a study combining post-mortem blunt dissections of a healthy 90 year old woman and diffusion tractography of a healthy young adult, Catani et al (2012) found that the AI connects directly, through U shaped tracts, to the triangular and orbital parts of the IFG, two regions that we also found to be significantly associated to verbal fluency in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a limited number of studies have used structural MRI to study language skills, including vocabulary acquisition (Lee et al, 2007), second language proficiency (Hosoda, Tanaka, Nariai, Honda, & Hanakawa, 2013; Mechelli et al, 2004), and speech perception and production (Bilodeau-Mercure, Lortie, Sato, Guitton, & Tremblay, 2014; Grogan, Green, Ali, Crinion, & Price, 2009; Tremblay, Dick, & Small, 2013). The study of spoken language production is complex because it depends upon a very large number of sensorimotor and cognitive processes.…”
Section: Introductionmentioning
confidence: 99%